Common Errors in the Management of Idiopathic Clubfeet Using the Ponseti Method: A Review of the Literature - Sean B. Youn; Ashish S. Ranade; Anil Agarwal; Mohan V. Belthur (MDPI AG, 2023)
Congenital talipes equinovarus is one of the most prevalent birth defects, affecting approximately 0.6 to 1.5 children per 1000 live births. Currently, the Ponseti method is the gold-standard treatment for idiopathic clubfeet, with good results reported globally. This literature review focuses on common errors encountered during different stages of the management of idiopathic clubfeet, namely diagnosis, manipulation, serial casting, Achilles tenotomy, and bracing. The purpose is to update clinicians and provide broad guidelines that can be followed to avoid and manage these errors to optimize short- and long-term outcomes of treatment of idiopathic clubfeet using the Ponseti method. A literature search was performed using the following keywords: "Idiopathic Clubfoot" (All Fields) AND "Management" OR "Outcomes" (All Fields). Databases searched included PubMed, EMBASE, Cochrane Library, Google Scholar, and SCOPUS (age range: 0-12 months). A full-text review of these articles was then performed looking for "complications" or "errors" reported during the treatment process. A total of 61 articles were included in the final review: 28 from PubMed, 8 from EMBASE, 17 from Google Scholar, 2 from Cochrane Library, and 6 from SCOPUS. We then grouped the errors encountered during the treatment process under the different stages of the treatment protocol (diagnosis, manipulation and casting, tenotomy, and bracing) to facilitate discussion and highlight solutions. While the Ponseti method is currently the gold standard in clubfoot treatment, its precise and intensive nature can present clinicians, health care providers, and patients with potential problems if proper diligence and attention to detail is lacking. The purpose of this paper is to highlight common mistakes made throughout the Ponseti treatment protocol from diagnosis to bracing to optimize care for these patients.